Spiraling elliptic hollow beams with cross phase. (16th March 2023) - Liang, Guo; Shu, Fangjie; Ma, Shaoshuo; Cheng, Wenjing; Sun, Chunzhi
Abstract: We introduced a class of spiraling elliptic hollow beams with the cross phase. Due to the cross phase, the spiraling elliptic hollow beams exhibit three key characteristics, having the elliptic peak ring, carrying the orbital angular momentum (OAM), and performing rotations. We investigated both linear and nonlinear evolutions of the spiraling elliptic hollow beams, and found they can propagate stably, thanks to the cross phase. Especially, we obtained the breather states of spiraling elliptic hollow beams in nonlocally nonlinear medium, and could handily control the rotation by changing optical powers. We discussed both the OAM property and optical force property. By using the spiraling elliptic hollow beams, we can achieve a jointly multiple manipulation on particles at the same time. In one step, we can trap and simultaneously rotate the particles.